Damned if you do, damned if you don't: How formerly incarcerated men navigate the labor market with prison credentials - Lindsay, Sadé L. (Criminology, 2022)
Although employment is central to successful reentry, formerly incarcerated people struggle to find work because of criminal stigma, poor education, and sparse work histories. Prison credentials are proposed as one solution to alleviate these challenges by signaling criminal desistance and employability. Evidence regarding their efficacy, however, is inconsistent. In this article, I develop a novel explanation—the prison credential dilemma—highlighting the numerous and contradictory ways employers may interpret prison credentials as positive and negative signals. Drawing on 50 qualitative interviews with formerly incarcerated men in Franklin County, Ohio, I examine how the prison credential dilemma and the uncertainty it produces shape their job search strategies and pathways to employment. I find that participants concealed or obscured institutional affiliations of prison credentials on job applications to signal employability rather than their criminal records. In job interviews, however, prison credentials were used to divert conversations away from their criminal record toward skills and criminal desistance via the use of redemptive narratives. Participants also attempted to acquire credentials outside of prison and/or pursued temporary, precarious jobs, aspiring for such physically strenuous and poorly paid work to materialize into stable employment. This study has implications for prison programming as well as policies and practices aiming to improve reentry outcomes.